The Degradation Analysis of XLPE Materials Under Thermal Aging: A Comprehensive Study Through Partial Discharge Measurements and Structural Characterization Techniques - Camalov, Mehti; Akin, Firat; Hashimov, Arif; Arikan, Oktay; Orucov, Allahverdi; Guliyev, Musafir (SPRINGER, 2024)
This article focuses on the impact of thermal aging on the insulation material used in cross-linked polyethylene (XLPE) cables. During the experimental process, the samples are subjected to thermal aging at 120 degrees C for 450 h in total. The impact of thermal stress on insulation quality is analyzed through partial discharge (PD) parameters. Accordingly, the average PD charge of peroxide and silane-added samples increased by 72% and 37%, respectively. Also, their partial discharge inception voltages decreased by 9% and 12.5%, respectively. For investigation of the root causes of the increase in partial discharge activity, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and ultraviolet-visible (UV-Vis) spectrophotometers are used. The structural changes caused by thermal aging were characterized through FTIR spectroscopy as the formation of new chemical bonds, chain degradation and increased absorption of hydroxyl and carbonyl groups. Additionally, XRD analysis showed alterations in crystallization degree, while UV-Vis spectral analysis demonstrated higher absorbances and a decrease in band gap energies for peroxide and silane-added XLPE samples, respectively, to 3.8 eV and 3.36 eV after thermal aging.
Keywords: Thermal aging; Insulation degradation; XLPE; Partial discharge; Characterization techniques; INSULATION SYSTEMS; SPACE-CHARGE; CABLE; NANOCOMPOSITES; BEHAVIOR; RESIN; Materials Science